How does Social Media Platforms of Facebook and Twitter used during COVID-19 Vaccination Campaign? A Study in West Sumatera - Novia Amirah Azmi; Annisa Weriframayeni; Eda Elysia; Aqil Teguh Fathani; Agustiyara Agustiyara (Universitas Teuku Umar, 2023)
This study aims to see the effectiveness social media platforms campaigning COVID-19 vaccination program in West Sumatra. This result provides new suggestions to interest actors to emphasize the dissemination of information through one of their social media. Measuring the effectiveness of communication is carried out by the recipient of the message, the source of the message, and the content of the message. Mixed methods research with the help of NVIVO 12+ analysis was conducted to give actual results. Sources of data obtained from community activities using Facebook and Twitter. The study's results showed a significant difference in the age of users on Facebook and Twitter; Facebook users were dominated by users less than 18 years and more than 50 years which affected the message delivery and message content for the vaccine campaign. Information changes often occur on Facebook because many users change information and make requests not to vaccinate. This call was also followed by bad news which assumed that vaccination would have a bad impact in the long term. Twitter users are more open and understand the information that circulates on social media, thus there are less opportunities to change information and spread falsehoods. Twitter users' favorable attitudes and actions when communicating on social media demonstrate that information distribution is more about a sense of security and comfort. The two platforms have been the most popular tools for public evaluation since individuals use social media more than they do traditional kinds of media.